2003
DOI: 10.1143/jjap.42.4837
|View full text |Cite
|
Sign up to set email alerts
|

Detection Improvement for Electron Energy Spectra for Surface Analysis Using a Field Emission Scanning Tunneling Microscope

Abstract: This paper focuses on a frequency-weighted hybrid adaptive control with application to simultaneous precision positioning and vibration suppression of smart composite structures. Following the introduction of the structure and materials system of an active composite panel (ACP) with a surface-mounted and two embedded piezoelectric ceramic patches, the sensor selection for the purpose of precision positioning or vibration control is discussed, and the function assignment of a laser displacement sensor as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The combination of the scanning probe technique and the electron energy spectroscopy technique is a promising way to resolve this problem. Great efforts have been made by several groups, such as Miyatake et al, 9,10) Tomitori et al, [11][12][13][14] Palmer et al, [15][16][17][18][19] and our group. [20][21][22] In these studies, the STM tip is used as a field emission electron source and the elemental identification can be achieved by measuring the energy spectra of the electrons backscattered from the sample surface stimulated by the field emission electrons from the STM tip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the scanning probe technique and the electron energy spectroscopy technique is a promising way to resolve this problem. Great efforts have been made by several groups, such as Miyatake et al, 9,10) Tomitori et al, [11][12][13][14] Palmer et al, [15][16][17][18][19] and our group. [20][21][22] In these studies, the STM tip is used as a field emission electron source and the elemental identification can be achieved by measuring the energy spectra of the electrons backscattered from the sample surface stimulated by the field emission electrons from the STM tip.…”
Section: Introductionmentioning
confidence: 99%
“…However, a strong electric field will be introduced between the STM tip and the sample surface, which will severely suppress the emitted electrons from the sample surface and make them difficult to be detected. The work of both Miyatake et al 9,10) and Tomitori et al [11][12][13][14] have approved that an unscreened STM tip is inapplicable for the measurement of the Auger electron energy spectra (AES) as the relative low energy of Auger electrons compared to the biasing voltage applied to the tip-sample. A tip shield is thus necessary for these kinds of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported electron energy spectra with STM images, including electron energy loss spectroscopy (EELS), obtained using STM combined with an energy analyzer. [8][9][10][11][12][13][14][15] In our previous reports, we have successfully demonstrated that a buildup [111]-oriented W tip 16,17) has several advantageous points for this method combined with STM to stabilize the field emission current and confine an irradiation area on a sample just below the sharpened tip to improve spatial resolution. 8,10,11,14) The buildup process, including field emission microscopy (FEM) techniques, can be carried out in our STM head, where the tip is biased at a high voltage and heated; we called our STM, field-emission (FE)-STM.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, STM is limited in its capacity to provide information on the chemical nature of the atoms it images. Several groups are developing STMbased techniques to obtain additional information, e.g., scanning probe energy loss spectroscopy ͑SPELS͒, 2-9 field emission STM, [10][11][12][13][14][15] and STM Auger electron energy spectroscopy 16,17 as well as STM low-energy electron diffraction. [18][19][20][21] The tips in these modified instruments typically operate in field emission mode, creating a local electron flux above the vacuum level, E vac .…”
mentioning
confidence: 99%
“…Electrochemically etched tungsten tips mounted within a chromium-coated borosilicate tube 16,20 and a coaxial gold-plated macroscopic tip holder have been explored previously. 12 However, these devices only shield the electric field macroscopically. Ideally the field should be excluded to within a few microns of the tip-surface junction.…”
mentioning
confidence: 99%